The Effect of Utilization of Information Technology and Work Facilities on Operational Performance Through Employee Performance at Coffee Shop in Tasikmalaya City - Dian Kurniawan; Lucky Radi Rinandiyana; Tine Badriatin (Enrichment : Journal of Management, 2022)
The business environment is an important factor that will affect the running of a business. Changes in the business environment occur at various scales. There are times when this change so massively affects the business environment, so it is called a mega shift. Mega shifts that occur sometimes are in different time spans, but sometimes coincide. One of the mega shifts that occur is an increase in the leisure economy where people, especially the millennial generation, prefer experience-based economic activities. This study aims to determine the effect of information technology on employee performance, the effect of work facilities on employee performance, the effect of the use of information technology and work facilities on employee performance and employee performance mediating the effect of using information technology and work facilities on operational performance. The research method used is a survey of 116 respondents. Quantitative data processing method using Partial Least Square (PLS) analysis using Smart PLS 3.0 tool. The results show that (1) Information technology has an effect on employee performance in coffeeshops. If information technology increases, it will be followed by an increase in employee performance, (2) Work facilities affect the performance of employees in the coffeeshop. If work facilities increase, it will be followed by an increase in employee performance, (3) Information technology and work facilities have an effect on employee performance in coffeeshops. If information technology and work facilities increase, it will be followed by an increase in employee performance, (4) Employee performance mediates the effect of the use of information technology and work facilities on operational performance.